2017
DOI: 10.2320/matertrans.m2016319
|View full text |Cite
|
Sign up to set email alerts
|

Induction Brazing of 304 Stainless Steel with a Metalloid-Free Ni-Zr-Ti-Al-Sn Amorphous Foil

Abstract: The feasibility of a novel metalloid-free Ni 57 Zr 20 Ti 17 Al 5 Sn 1 (at.%) amorphous ller metal for 304 SS brazing was investigated by induction brazing. The joining process can be completed within seconds in argon atmosphere due to the sensitive response of induction heating. The effects of joining time on the microstructure of joints and the joint shear strength were investigated. The results indicate that the joints brazed for 5 s and 10 s exhibit good wetting between the base metal and the ller metal. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Various kinds of industrial applications have been reported, including hardening, 2) hot forging 3) , die casting 4) , liquid-solid casting, 5) shrinkage fitting, 6) brazing, 7) and the Czochralski method for crystal growth. 8) Metal-metal bonding, 9) silicon-grass bonding, 10) and bonding and dismantling processes 11) have been conducted with IH. Recently, IH has been combined with other processes to improve material characteristics; for example, it was combined with gas nitriding to improve tribological properties 12) and with shot peening to increase pitting potential.…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of industrial applications have been reported, including hardening, 2) hot forging 3) , die casting 4) , liquid-solid casting, 5) shrinkage fitting, 6) brazing, 7) and the Czochralski method for crystal growth. 8) Metal-metal bonding, 9) silicon-grass bonding, 10) and bonding and dismantling processes 11) have been conducted with IH. Recently, IH has been combined with other processes to improve material characteristics; for example, it was combined with gas nitriding to improve tribological properties 12) and with shot peening to increase pitting potential.…”
Section: Introductionmentioning
confidence: 99%